Impedance spectroscopy properties of polypyrrole doped with boric acid - Yakuphanoğlu, Fahrettin; Yahia, I. S.; Senkal, B. F.; Sakr, G. B.; Farooq, W. A. (Elsevier Science Sa, 2011)
The electrical conductivity and dielectric properties of polypyrrole doped with boric acid have been investigated. The direct current conductivity (dc) of the polymer increases with increasing temperature. The alternating current (ac) conductivity of the polymer obeys the power law, i.e., sigma(ac)(omega) = A omega(s). The alternating conductivity of polypyrrole doped with boric acid is controlled by the correlated barrier hopping model. The activation energy for alternating current mechanism decreases with increasing frequency which confirms the hopping conduction to the dominant mechanism as compared with the dc activation energy. The density of localized states N(E-F) for polypyrrole doped with boric acid was in the range of 2.5-9.2 x 10(22) cm(-3) for various temperatures. The dielectric relaxation mechanism was explained on the basis of complex dielectric modulus. The imaginary modulus plot at different temperatures shows a dielectric mechanism with non-Debye relaxation. Boric acid can be a good candidate for controlling the electrical conductivity of the conducting polymer. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer; Polypyrrole doped with boric acid; dc and ac electrical conductivities; Activation energy; Conduction mechanism; Impedance spectroscopy; Dielectric properties and relaxation time